Олександр Пантелеймонович Руденко (до 80-річчя від дня народження) - Bulavin, L.; Cholpan, P.; Zabashta, Yu.; Kulish, M.; Chalyi, O.; Sysoev, V.; Poperenko, L.; Alekseev, O.; Malomuzh, M.; Svechnikova, O.; Moskalenko, Yu.; Khorolskyi, O. (Publishing house "Academperiodika", 2018)
-